2005
DOI: 10.1016/j.jvs.2005.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of abdominal aortic aneurysms evaluated by tissue Doppler imaging: Correlation with aneurysm size

Abstract: Compliance parameters can easily be measured during routine AAA ultrasound monitoring using the tissue Doppler imaging system. The study showed an increase in MMSD and segmental compliance as well as a nonsignificant trend toward increased distensibility (decreased Ep and stiffness) with increased AAA diameter. A change in dispersion of AAA distensibility may appear around 45 mm in diameter, but a larger study will be needed to clarify this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…Several non-invasive modalities are currently compared to IVUS [14]. Magnetic resonance elastography can be used for measuring tissue strain, and result similar to the current report have been described in studies of the aorta or carotid arteries, which are larger and easier to image [15][16][17]. More recently, coronary MDCT has been compared to IVUS for the assessment of coronary morphology [18][19][20][21].…”
supporting
confidence: 66%
“…Several non-invasive modalities are currently compared to IVUS [14]. Magnetic resonance elastography can be used for measuring tissue strain, and result similar to the current report have been described in studies of the aorta or carotid arteries, which are larger and easier to image [15][16][17]. More recently, coronary MDCT has been compared to IVUS for the assessment of coronary morphology [18][19][20][21].…”
supporting
confidence: 66%
“…Long et al demonstrated a correlation between compliance and aortic size using TDI. There was significant positive linear relationship between maximum diameter and segmental compliance but not with the pressure strain modulus or stiffness [14]. Further studies are now required to assess whether compliance measured during routine AAA ultrasound monitoring using TDI could be a predictor of expansion.…”
Section: Ultrasoundmentioning
confidence: 91%
“…It is the fractional change in vessel cross sectional area divided by the change in distending pressure [14]. C = ∆A/∆p or C = 1/(PWV) 2 ρ ρ = 1055.103 [kg/m 3 ] denotes the mass density of blood that is assumed to be constant.…”
Section: Compliance (C)mentioning
confidence: 99%
“…Later studies reported that large aneurysms tended to be stiffer than smaller, but with large variations for equally sized aneurysms (Wilson et al, 1999), and that increased distensibility over time (compared to baseline) indicated significantly reduced time to rupture (Wilson et al, 2003). However, Long et al (2005) used tissue Doppler imaging, and reported a trend toward increased distensibility with increased AAA diameter. Ultrasonic tracking of diameter has demonstrated that the aorta is stiffer in men than age-matched women, that stiffness increases with age, and that aneurysm tissue is much stiffer than normal aorta (Länne et al, 1992;Sonesson et al, 1993).…”
Section: Prediction Of Growth and Rupturementioning
confidence: 99%